Treatment strategies for clozapine-induced hypotension: a systematic review - Timothy David Tanzer; Thomas Brouard; Samuel Dal Pra; Nicola Warren; Michael Barras; Steve Kisely; Emily Brooks; Dan Siskind (Therapeutic Advances in Psychopharmacology, 2022)
Background: Clozapine is the most effective medication for treatment–refractory schizophrenia but is associated with significant adverse drug effects, including hypotension and dizziness, which have a negative impact on quality of life and treatment compliance. Available evidence for the management of clozapine-induced hypotension is scant. Objectives: Due to limited guidance on the safety and efficacy of pharmacological treatments for clozapine-induced hypotension, we set out to systematically review and assess the evidence for the management of clozapine-induced hypotension and provide guidance to clinicians, patients, and carers. Design: We undertook a systematic review of the safety and efficacy of interventions for clozapine-induced hypotension given the limited available evidence. Data Sources and Methods: PubMed, Embase, PsycINFO, CINAHL, and the Cochrane trial Registry were searched from inception to November 2021 for literature on the treatment strategies for clozapine-induced hypotension and dizziness using a PROSPERO pre-registered search strategy. For orthostatic hypotension, we developed a management framework to assist in the choice of intervention. Results: We identified nine case studies and four case series describing interventions in 15 patients. Hypotension interventions included temporary clozapine dose reduction, non-pharmacological treatments, and pharmacological treatments. Midodrine, fludrocortisone, moclobemide and Bovril ® combination, and etilefrine were associated with improvement in symptoms or reduction in orthostatic hypotension. Angiotensin II, arginine vasopressin, and noradrenaline successfully restored and maintained mean arterial pressure in critical care situations. A paradoxical reaction of severe hypotension was reported with adrenaline use. Conclusion: Orthostatic hypotension is a common side effect during clozapine titration. Following an assessment of the titration schedule, salt and fluid intake, and review of hypertensive and nonselective α1-adrenergic agents, first-line treatment should be a temporary reduction in clozapine dose or non-pharmacological interventions. If orthostatic hypotension persists, fludrocortisone should be trialled with monitoring of potassium levels and sodium and fluid intake. Midodrine may be considered second-line or where fludrocortisone is contraindicated or poorly tolerated. For patients on clozapine with hypotension in critical care settings, the use of adrenaline to maintain mean arterial pressure should be avoided. Registration: PROSPERO (Registration No. CRD42020191530)